Common Fixed Points of Single-Valued and Multi-Valued Mappings in S-Metric Spaces - Akbar Pourgholam; Masoud Sabbaghan; Fatemeh Taleghani (IndoMS, 2022)
In this paper, the notion of limit property (-Tayyab kamran, 2004-) and common limit property (-Yicheng Liu & Jun Wu & Zhixiang Li, 2005-) for singlevalued and multi-valued mappings on metric spaces are generalized to S-metric spaces. This idea is used to make some common fixed point theorems for singlevalued and multi-valued mappings by using a generalization of coincidence point in S-metric spaces. We give an example of an S-metric which is not continuous.